Tính
A) \(\dfrac{1}{6}-\dfrac{2}{3}.\dfrac{5}{4}\)
B) \(\dfrac{9}{3^{12}.27^6}\)
\(\dfrac{-1}{3}.\dfrac{2}{5}\)
\(\dfrac{-3}{7}.\dfrac{4}{15}\)
\(\dfrac{-9}{3}.\dfrac{15}{27}\)
\(\dfrac{-5}{6}.\)( -12 )
\(\dfrac{-12}{4}.\dfrac{8}{9}\)
\(-3.\dfrac{7}{6}\)
\(\dfrac{-15}{9}.\dfrac{27}{5}\)
\(-9.\dfrac{4}{27}\)
-2/15
-4/35
-5/3
10
-8/3
-7/2
-9
-4/3
Chúc em học giỏi
\(=\dfrac{-2}{15}\\ =\dfrac{-4}{35}\\ =-1\\ =10\\ =\dfrac{-8}{3}\\ =-7\\ =-9\\ =\dfrac{-4}{3}\)
Tính
a,\(\dfrac{3}{4}\) - \(\dfrac{1}{12}\) - \(\dfrac{1}{6}\) + 2 b,\(\dfrac{2}{5}\) + \(\dfrac{3}{10}\) + \(\dfrac{4}{5}\) - \(\dfrac{5}{6}\)
c, \(\dfrac{12}{25}\) : \(\dfrac{9}{32}\) \(\dfrac{16}{15}\) d, \(\dfrac{3}{5}\) x \(\dfrac{2}{7}\) x \(\dfrac{5}{6}\) : 5
a: =9/12-1/12-2/12+2=1/2+2=5/2
b: =(2/5+4/5+3/10)-5/6=6/5+3/10-5/6=15/10-5/6=3/2-5/6=9/6-5/6=4/6=2/3
c: \(=\dfrac{12}{25}\cdot\dfrac{32}{9}\cdot\dfrac{15}{16}=\dfrac{12}{9}\cdot\dfrac{32}{16}\cdot\dfrac{15}{25}=\dfrac{4}{3}\cdot\dfrac{3}{5}\cdot2=\dfrac{8}{5}\)
Tính
a.\(\dfrac{4}{9}+\dfrac{3}{7}\) \(\dfrac{3}{4}+\dfrac{7}{24}\) \(\dfrac{1}{3}+\dfrac{2}{9}+\dfrac{4}{27}\)
b.\(\dfrac{5}{6}-\dfrac{3}{8}\) \(\dfrac{7}{15}-\dfrac{11}{30}\) \(\dfrac{2}{3}+\dfrac{1}{6}-\dfrac{7}{12}\)
c.\(\dfrac{18}{25}\times\dfrac{15}{6}\) \(\dfrac{30}{49}:\dfrac{6}{7}\) \(\dfrac{1}{2}\times\dfrac{3}{4}:\dfrac{6}{5}\)
d.\(8\times\dfrac{3}{5}:\dfrac{12}{5}\) \(4:\dfrac{9}{5}:\dfrac{10}{3}\)
3 bn đầu tiên xong mik sẽ tick
a: 4/9+3/7=28/63+27/63=55/63
3/4+7/24=18/24+7/24=25/24
1/3+2/9+4/27=9/27+6/27+4/27=19/27
b: 5/6-3/8=20/24-9/24=11/24
7/15-11/30=14/30-11/30=3/30=1/10
2/3+1/6-7/12
=8/12+2/12-7/12
=3/12=1/4
c: 18/25*15/6=15/25*18/6=3*3/5=9/5
30/49:6/7=30/49*7/6=210/294=5/7
1/2*3/4:6/5=3/8*5/6=15/48=5/16
d: 8*3/5:12/5=24/5*5/12=2
4:9/5:10/3=4*5/9*3/10=2/3
Tính (theo mẫu).
Mẫu: \(2+\dfrac{1}{6}=\dfrac{12}{6}+\dfrac{1}{6}=\dfrac{13}{6};1-\dfrac{1}{4}=\dfrac{4}{4}-\dfrac{1}{4}=\dfrac{3}{4}\) |
a) \(1+\dfrac{4}{9}\) b) \(5+\dfrac{1}{2}\) c) \(3-\dfrac{5}{6}\) d) \(\dfrac{31}{7}-2\)
a) \(1+\dfrac{4}{9}=\dfrac{9}{9}+\dfrac{4}{9}=\dfrac{9+4}{9}=\dfrac{13}{9}\)
b) \(5+\dfrac{1}{2}=\dfrac{10}{2}+\dfrac{1}{2}=\dfrac{10+1}{2}=\dfrac{11}{2}\)
c) \(3-\dfrac{5}{6}=\dfrac{18}{6}-\dfrac{5}{6}=\dfrac{18-5}{6}=\dfrac{13}{6}\)
d) \(\dfrac{31}{7}-2=\dfrac{31}{7}-\dfrac{14}{7}=\dfrac{31-14}{7}=\dfrac{17}{7}\)
1) tính
a)\(9^{14}:\left(3^{12}.27^6\right)\)
B)\(\sqrt{\dfrac{4}{9}}+\left(\dfrac{-1}{2}\right)^3-|\dfrac{-2}{3}|\)
Tính hợp lý nếu có thể:
a) \(\dfrac{2}{9}+\dfrac{-3}{10}+\dfrac{-7}{10}\)
b) \(\dfrac{-11}{6}+\dfrac{2}{5}+\dfrac{-1}{6}\)
c) \(\dfrac{27}{13}-\dfrac{106}{111}+\dfrac{-5}{111}\)
d) \(\dfrac{12}{11}-\dfrac{-7}{19}+\dfrac{12}{19}\)
a, \(=\dfrac{2}{9}-\dfrac{10}{10}=\dfrac{2}{9}-1=-\dfrac{7}{9}\)
b, \(=-\dfrac{12}{6}+\dfrac{2}{5}=-2+\dfrac{2}{5}=-\dfrac{8}{5}\)
c, \(=\dfrac{27}{13}-1=\dfrac{14}{13}\)
d, \(=\dfrac{12}{11}+\dfrac{7}{19}+\dfrac{12}{19}=\dfrac{12}{11}+1=\dfrac{23}{11}\)
a) \(\dfrac{2}{9}+\dfrac{-3}{10}+\dfrac{-7}{10}\)
\(=\dfrac{2}{9}+\dfrac{-10}{10}=\dfrac{2}{9}-1=-\dfrac{7}{9}\)
b) \(\dfrac{-11}{6}+\dfrac{2}{5}+\dfrac{-1}{6}\)
\(=-2+\dfrac{2}{5}=-\dfrac{8}{5}\)
a,\(=\dfrac{2}{9}+\left(\dfrac{-3}{10}+\dfrac{-7}{10}\right)=\dfrac{2}{9}+\left(-1\right)=\dfrac{-7}{9}\)
b,\(=\left(\dfrac{-11}{6}+\dfrac{-1}{6}\right)+\dfrac{2}{5}=-2+\dfrac{2}{5}=\dfrac{-8}{5}\)
c,\(=\dfrac{27}{13}-\left(\dfrac{106}{111}+\dfrac{-5}{111}\right)=\dfrac{27}{13}-1=\dfrac{14}{13}\)
Tính (theo mẫu).
Mẫu: \(\dfrac{1}{2}-\dfrac{5}{12}=\dfrac{6}{12}-\dfrac{5}{12}=\dfrac{6-5}{12}=\dfrac{1}{12}\) |
a) \(\dfrac{3}{4}-\dfrac{1}{8}\) b) \(\dfrac{2}{6}-\dfrac{5}{18}\) c) \(\dfrac{2}{5}-\dfrac{3}{20}\)
a) \(\dfrac{3}{4}-\dfrac{1}{8}=\dfrac{6}{8}-\dfrac{1}{8}=\dfrac{6-1}{8}=\dfrac{5}{8}\)
b) \(\dfrac{2}{6}-\dfrac{5}{18}=\dfrac{6}{18}-\dfrac{5}{18}=\dfrac{6-5}{18}=\dfrac{1}{18}\)
c) \(\dfrac{2}{5}-\dfrac{3}{20}=\dfrac{8}{20}-\dfrac{3}{20}=\dfrac{8-3}{20}=\dfrac{5}{20}=\dfrac{1}{4}\)
Thực hiện phép tính
a)\(\dfrac{5^{16}.27^{7}}{125^{5}.9^{11}}\)
b)\((-0,2)^{2}.5-\dfrac{2^{13}.27^{3}}{4^{6}.9^{5}}\)
c)\(\dfrac{5^{6}+2^{2}.25^{3}+2^{3}.125^{2}}{26.5^{6}}\)
\(a,\dfrac{5^{16}\cdot27^7}{125^5\cdot9^{11}}=\dfrac{5^{16}\cdot\left(3^3\right)^7}{\left(5^3\right)^5\cdot\left(3^2\right)^{11}}\)
\(=\dfrac{5^{16}\cdot3^{21}}{5^{15}\cdot3^{22}}=\dfrac{5}{3}\)
\(b,\left(-0,2\right)^2\cdot5-\dfrac{2^{13}\cdot27^3}{4^6\cdot9^5}\)
\(=0,04\cdot5-\dfrac{2^{13}\cdot\left(3^3\right)^3}{\left(2^2\right)^6\cdot\left(3^2\right)^5}\)
\(=0,2-\dfrac{2^{13}\cdot3^9}{2^{12}\cdot3^{10}}\)
\(=0,2-\dfrac{2}{3}\)
\(=-\dfrac{7}{15}\)
\(c,\dfrac{5^6+2^2\cdot25^3+2^3\cdot125^2}{26\cdot5^6}\)
\(=\dfrac{5^6+2^2\cdot\left(5^2\right)^3+2^3\cdot\left(5^3\right)^2}{5^6\cdot26}\)
\(=\dfrac{5^6+4\cdot5^6+8\cdot5^6}{5^6\cdot26}\)
\(=\dfrac{5^6\left(1+4+8\right)}{5^6\cdot26}\)
\(=\dfrac{13}{26}\)
\(=\dfrac{1}{2}\)
#\(Toru\)
\(a,\dfrac{5^{16}.27^7}{125^5.9^{11}}=\dfrac{\left(5^2\right)^8.9^7.3^7}{25^5.5^5.9^{11}}\\ =\dfrac{25^8.9^7.\left(3^2\right)^3.3}{25^5.\left(5^2\right)^2.5.9^{11}}=\dfrac{25^8.9^7.9^3.3}{25^5.25^2.5.9^{11}}\\ =\dfrac{25^8.9^{10}.3}{25^7.5.9^{11}}=\dfrac{25^7.9^{10}.25.3}{25^7.9^{10}.5.9}\\ =\dfrac{25.3}{5.9}=\dfrac{5.5.3}{5.3.3}=\dfrac{5}{3}\)
Bài 1. Tính
A= \(\left(8\dfrac{2}{7}-4\dfrac{2}{7}\right)-3\dfrac{4}{9}\)
B= \(\left(10\dfrac{2}{9}-6\dfrac{2}{9}\right)+2\dfrac{3}{5}\)
Bài 2. Tính
a) \(5\dfrac{1}{2}.3\dfrac{1}{4}\) b) \(6\dfrac{1}{3}:4\dfrac{2}{9}\) c) \(4\dfrac{3}{7}.2\)
`A=(8 2/7-4 2/7)-3 4/9`
`=8+2/7-4-2/7-3-4/9`
`=4-3-4/9`
`=1-4/9=5/9`
`B=(10 2/9-6 2/9)+2 3/5`
`=10+2/9-6-2/9+2+3/5`
`=4+2+3/5`
`=6+3/5=33/5`
Bài 2:
`a)5 1/2*3 1/4`
`=11/2*13/4`
`=143/8`
`b)6 1/3:4 2/9`
`=19/3:38/9`
`=19/3*9/38=3/2`
`c)4 3/7*2`
`=31/7*2`
`=62/7`
Bài 1:
\(A=\left(8\dfrac{2}{7}-4\dfrac{2}{7}\right)-3\dfrac{4}{9}\)
\(A=\left(\dfrac{58}{7}-\dfrac{30}{7}\right)-\dfrac{31}{9}\)
\(A=4-\dfrac{31}{9}\)
\(A=\dfrac{5}{9}\)
\(B=\left(10\dfrac{2}{9}-6\dfrac{2}{9}\right)+2\dfrac{3}{5}\)
\(B=\left(\dfrac{92}{9}-\dfrac{56}{9}\right)+\dfrac{13}{5}\)
\(B=4+\dfrac{13}{5}\)
\(B=\dfrac{33}{5}\)
Bài 2:
a) \(5\dfrac{1}{2}.3\dfrac{1}{4}=\dfrac{11}{2}.\dfrac{13}{4}=\dfrac{11.13}{2.4}=\dfrac{143}{8}\)
b) \(6\dfrac{1}{3}:4\dfrac{2}{9}=\dfrac{19}{3}:\dfrac{38}{9}=\dfrac{19}{3}.\dfrac{9}{38}=\dfrac{3}{2}\)
c) \(4\dfrac{3}{7}.2=\dfrac{31}{7}.2=\dfrac{31.2}{7}=\dfrac{62}{7}\)